Silver-coated iron low-temperature silver paste and preparation method and application thereof
By using silver-coated iron powder instead of pure silver powder and adding a curing agent, the problem of high production cost of low-temperature conductive silver paste is solved, efficient solidification and performance improvement of low-temperature silver paste are achieved, and the energy consumption of battery production is reduced.
Patent Information
- Application Number
- CN202411722836.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the production cost of low-temperature conductive silver paste is high, which limits the application of HJT heterojunction solar cells.
By using high-temperature resistant and low-priced silver-coated iron powder instead of pure silver powder to prepare conductive paste, and adding curing accelerators and curing agents to the silver paste, efficient curing of low-temperature silver paste is achieved.
The production cost of low -temperature silver pulp was greatly reduced, and the performance reached the level of sterling silver slurry. At the same time, it was solidified 30 minutes at 190 to 200 ° C, reducing energy consumption during the battery production process.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solar cells, and in particular relates to a silver-coated iron low-temperature silver paste and a preparation method and application thereof. Background Art
[0002] Heterojunction solar cells are currently a more efficient type of crystalline silicon solar cell, which combines the characteristics of crystalline silicon cells and silicon-based thin-film cells, and has the advantages of short manufacturing process, low process temperature, high conversion efficiency and high power generation. Due to the small temperature degradation coefficient of heterojunction solar cells and double-sided power generation, under the same area conditions, the annual power generation can be 15-30% higher than that of ordinary polycrystalline silicon cells, so it has great market potential.
[0003] In the prior art, due to the limitation of low temperature process, only low temperature conductive silver paste can be used when printing the first collector and the second collector using a screen plate. The production cost of low temperature conductive silver paste is high. Therefore, the application of HJT heterojunction solar cells is restricted in many aspects due to its high production cost. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, an embodiment of the present invention provides a silver-coated iron low-temperature silver paste, which greatly reduces the production cost of the low-temperature silver paste by using high-temperature resistant and low-priced silver-coated iron powder instead of pure silver powder to prepare the conductive paste, and the performance can reach the level of pure silver paste.
[0005] The silver-coated iron low-temperature silver paste of the embodiment of the present invention includes: 23-85wt% of silver powder, 8-45wt% of silver-coated iron powder, 3-8wt% of epoxy resin, 0.1-2wt% of curing agent, 0.5-2wt% of curing accelerator, 4-10wt% of solvent, and 0.5-3wt% of additives.
[0006] The advantages and technical effects brought by the silver-coated iron low-temperature silver paste of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, the conductive paste is prepared by using high-temperature resistant and low-cost silver-coated iron powder instead of pure silver powder, which greatly reduces the production cost of the low-temperature silver paste, and the performance can reach the level of pure silver paste; 2. In the embodiment of the present invention, the curing accelerator and curing agent added to the silver paste are used in combination, which can make the low-temperature silver paste solidify within 30 minutes at 190-200°C, thereby reducing the energy consumption in the battery production process.
[0007] In some embodiments, the silver powder includes spherical silver powder and flake silver powder.
[0008] In some embodiments, the spherical silver powder has an average particle size of 0.1 to 0.8 μm and a tap density of 4 to 7 g / cm3;
[0009] And / or, the average particle size of the flaky silver powder is 2 to 5 μm, and the tap density is 4 to 7 g / cm3.
[0010] In some embodiments, the mass ratio of the spherical silver powder to the flake silver powder is 1:1 to 1:4.
[0011] In some embodiments, the silver-coated iron powder has a particle size of 1 to 4 μm.
[0012] In some embodiments, the silver content in the silver-coated iron powder is 10-30 wt %.
[0013] In some embodiments, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, and hydrogenated bisphenol F epoxy resin;
[0014] And / or, the curing agent includes at least one of blocked polyisocyanate and phenolic resin;
[0015] And / or, the curing accelerator includes at least one of an imidazole compound and a boron trifluoride ethylamine complex;
[0016] and / or, the solvent comprises at least one of terpineol, diethylene glycol butyl ether acetate and dipropylene glycol;
[0017] And / or, the additive includes at least one of a defoamer, a dispersant, a wetting agent, an anti-aging agent, and a leveling agent.
[0018] The embodiment of the present invention also provides a method for preparing a silver-clad iron low-temperature silver paste, comprising the following steps:
[0019] (1) mixing a solvent and a curing agent under magnetic stirring to obtain a first mixture;
[0020] (2) mixing the first mixture obtained in step (1) with epoxy resin in a double planetary mixer, and then adding silver powder, silver-coated iron powder, curing accelerator and additives to obtain a second mixture;
[0021] (3) The second mixture obtained in step (2) is dispersed on a three-roll mill, and then filtered and de-bubbled.
[0022] In some embodiments, in step (2), the mixing temperature in the dual planetary mixer is 0 to 30°C;
[0023] And / or, in the step (3), the number of dispersion times on the three-roll mill is 3 to 5 times.
[0024] The embodiments of the present invention also provide the use of the above-mentioned silver-coated iron low-temperature silver paste or the silver-coated iron low-temperature silver paste prepared by the above-mentioned method in a silicon heterojunction battery. DETAILED DESCRIPTION
[0025] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.
[0026] The silver-coated iron low-temperature silver paste of the embodiment of the present invention includes: 23-85wt% of silver powder, 8-45wt% of silver-coated iron powder, 3-8wt% of epoxy resin, 0.1-2wt% of curing agent, 0.5-2wt% of curing accelerator, 4-10wt% of solvent, and 0.5-3wt% of additives.
[0027] The silver-coated iron low-temperature silver paste of the embodiment of the present invention uses high-temperature resistant and low-cost silver-coated iron powder instead of pure silver powder to prepare the conductive paste, which greatly reduces the production cost of the low-temperature silver paste, and the performance can reach the level of pure silver paste; in the embodiment of the present invention, the curing accelerator and curing agent added to the silver paste are used in combination, so that the low-temperature silver paste can be cured within 30 minutes at 190-200°C, thereby reducing the energy consumption in the battery production process.
[0028] In some embodiments, preferably, the silver powder includes spherical silver powder and flake silver powder.
[0029] In the embodiment of the present invention, the silver powder is defined as a mixture of spherical silver powder and flaky silver powder. The spherical silver powders are in point-to-point contact with each other, have fluidity and rheology, and have good printing adaptability. The flaky silver powders are in surface or line contact with each other, which can improve the conductivity of the silver paste. The silver powder is formed by a mixture of spherical silver powder and flaky silver powder, and the spherical silver powder with a small diameter is used to fill the gaps in the flaky silver powder, further improving the density of the silver paste, and it is defined to have a higher tap density, so that the silver paste can reach a silver content of >90%.
[0030] In some embodiments, preferably, the average particle size of the spherical silver powder is 0.1 to 0.8 μm, such as 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, etc.; the tap density is 4 to 7 g / cm 3 , for example 4g / cm 3 , 4.5g / cm 3 , 5g / cm 3 , 5.5g / cm 3 , 6g / cm 3 、6.5g / cm 3 , 7g / cm 3 wait.
[0031] In some embodiments, preferably, the average particle size of the flaky silver powder is 2 to 5 μm, such as 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc.; the tap density is 4 to 7 g / cm 3 , for example 4g / cm 3 , 4.5g / cm 3 , 5g / cm 3 , 5.5g / cm 3 , 6g / cm 3 、6.5g / cm 3 , 7g / cm 3 wait.
[0032] In some embodiments, preferably, the mass ratio of the spherical silver powder to the flaky silver powder is 1:1 to 1:4, for example, 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, etc.
[0033] In the embodiment of the present invention, the mass ratio of spherical silver powder and flaky silver powder is optimized, so that the low-temperature silver paste can have good printing adaptability and conductivity at the same time; if the amount of spherical silver powder is too much, the conductivity of the silver paste will be reduced; if the amount of spherical silver powder is too little, the printing adaptability of the silver paste will be deteriorated.
[0034] In some embodiments, preferably, the particle size of the silver-coated iron powder is 1 to 4 μm, for example, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, etc.
[0035] In some embodiments, preferably, the silver content in the silver-coated iron powder is 10-30wt%, for example, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%, etc.
[0036] In some embodiments, preferably, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, and hydrogenated bisphenol F epoxy resin;
[0037] And / or, the curing agent includes at least one of blocked polyisocyanate and phenolic resin;
[0038] And / or, the curing accelerator includes at least one of an imidazole compound and a boron trifluoride ethylamine complex;
[0039] and / or, the solvent comprises at least one of terpineol, diethylene glycol butyl ether acetate and dipropylene glycol;
[0040] And / or, the additive includes at least one of a defoamer, a dispersant, a wetting agent, an anti-aging agent, and a leveling agent.
[0041] The embodiment of the present invention also provides a method for preparing a silver-clad iron low-temperature silver paste, comprising the following steps:
[0042] (1) mixing a solvent and a curing agent under magnetic stirring to obtain a first mixture;
[0043] (2) mixing the first mixture obtained in step (1) with epoxy resin in a double planetary mixer, and then adding silver powder, silver-coated iron powder, curing accelerator and additives to obtain a second mixture;
[0044] (3) The second mixture obtained in step (2) is dispersed on a three-roll mill, and then filtered and de-bubbled.
[0045] In some embodiments, preferably, in step (2), the mixing temperature in the double planetary mixer is 0 to 30°C;
[0046] And / or, in the step (3), the number of dispersion times on the three-roll mill is 3 to 5 times.
[0047] The embodiments of the present invention also provide the use of the above-mentioned silver-coated iron low-temperature silver paste or the silver-coated iron low-temperature silver paste prepared by the above-mentioned method in a silicon heterojunction battery.
[0048] The technical solution of the present invention is described in detail below in conjunction with specific embodiments.
[0049] Example 1
[0050] (1) Weigh 4.20 g of blocked polyisocyanate into a beaker, add 24.6 g of diethylene glycol butyl ether acetate, place in a magnetic stirrer and heat to 60° C. in a constant temperature water bath, stir continuously at a speed of 600 r / min until the phenolic resin is completely dissolved, keep warm for 1 hour after complete dissolution, cool and keep for later use, to obtain a first mixture;
[0051] (2) The first mixture and 15.2g of Taiwan Changchun bisphenol F epoxy resin BFE-170 were then stirred at 20°C by double planetary stirring, and 264.7g of silver powder, 94.4g of silver-coated iron powder, 5.3g of imidazole compound and 2.16g of defoamer were added under stirring. The silver powder includes spherical powder and flaky silver powder, wherein the spherical silver powder has an average particle size of 0.70μm and a tap density of 4.8g / cm 3 The average particle size of the flaky silver powder is 3.67 μm, and the tap density is 5.53 g / cm 3, the weight ratio of spherical silver powder to flake silver powder is 1:2, the particle size of the silver-coated iron powder is 2 μm, and the silver content in the silver-coated iron is 15wt%;
[0052] (3) The mixture is dispersed three times on a three-roll disperser and filtered and treated to remove bubbles to obtain a low-temperature silver paste for silicon heterojunction solar cells.
[0053] Example 2
[0054] (1) Weigh 4.56 g of phenolic resin into a beaker, add 16.82 g of terpineol, place in a magnetic stirrer and heat to 60° C. in a constant temperature water bath, stir continuously at a speed of 800 r / min until the phenolic resin is completely dissolved, keep warm for 1 hour after complete dissolution, cool and keep for later use, to obtain a first mixture;
[0055] (2) The first mixture and 16.4 g of Nan Ya bisphenol F epoxy resin NPEF-170 were then stirred at 25°C by double planetary stirring, and 214.6 g of silver powder, 114.5 g of silver-coated iron powder, 3.0 g of boron trifluoride ethylamine complex and 3.84 g of defoamer were added under stirring. The silver powder includes spherical powder and flaky silver powder, wherein the spherical silver powder has an average particle size of 0.3 μm and a tap density of 5.6 g / cm 3 The average particle size of the flaky silver powder is 4.56μm, and the tap density is 4.27g / cm 3 The weight ratio of spherical silver powder to flaky silver powder is 1:1, the particle size of the silver-coated iron powder is 3 μm, and the silver content in the silver-coated iron is 26 wt%.
[0056] (3) The mixture is dispersed three times on a three-roll disperser and filtered and treated to remove bubbles to obtain a low-temperature silver paste for silicon heterojunction solar cells.
[0057] Comparative Example 1
[0058] The preparation process of this comparative example is the same as that of Example 1, except that in step (2), no silver-coated iron powder is added and the amount of silver powder added is 359.1 g.
[0059] The performance of the silver-clad iron low-temperature silver paste prepared in Examples 1 to 2 and Comparative Example 1 was tested, and the results are shown in Table 1:
[0060] Table 1
[0061]
[0062] The silver-clad iron low-temperature silver pastes prepared in Examples 1 to 2 and Comparative Example 1 were subjected to performance tests, and the results are shown in Table 2:
[0063] Table 2
[0064] [Isc(A)] <![CDATA[[Jsc(mA / cm 2 )]]]> [Voc(V)] [FF(%)] [Eff(%)] Example 1 9.327 38.19 0.7453 83.87 23.56 Example 2 9.490 38.30 0.7503 83.82 23.73 Comparative Example 1 9.349 38.21 0.7460 83.91 23.59
[0065] Note: Isc refers to the short-circuit current of the battery, Jsc refers to the short-circuit current density of the battery, Voc refers to the open-circuit voltage of the battery, FF refers to the fill factor of the battery, and Eff refers to the conversion efficiency of the battery.
[0066] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0067] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A silver-clad iron low-temperature silver paste, characterized in that: include: Silver powder 23-85wt%, silver-coated iron powder 8-45wt%, epoxy resin 3-8wt%, curing agent 0.1-2wt%, curing accelerator 0.5-2wt%, solvent 4-10wt%, additive 0.5-3wt%.
2. The silver-clad iron low-temperature silver paste according to claim 1, characterized in that: The silver powder includes spherical silver powder and flake silver powder.
3. The silver-clad iron low-temperature silver paste according to claim 2, characterized in that: The average particle size of the spherical silver powder is 0.1 to 0.8 μm, and the tap density is 4 to 7 g / cm3; And / or, the average particle size of the flaky silver powder is 2 to 5 μm, and the tap density is 4 to 7 g / cm3.
4. The silver-clad iron low-temperature silver paste according to claim 2 or 3, characterized in that: The mass ratio of the spherical silver powder to the flaky silver powder is 1:1 to 1:
4.
5. The silver-clad iron low-temperature silver paste according to claim 1, characterized in that: The particle size of the silver-coated iron powder is 1-4 μm.
6. The silver-clad iron low-temperature silver paste according to claim 1 or 5, characterized in that: The silver content in the silver-coated iron powder is 10-30wt%.
7. The silver-clad iron low-temperature silver paste according to claim 1, characterized in that: The epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, hydrogenated bisphenol A epoxy resin, and hydrogenated bisphenol F epoxy resin; And / or, the curing agent includes at least one of blocked polyisocyanate and phenolic resin; And / or, the curing accelerator includes at least one of an imidazole compound and a boron trifluoride ethylamine complex; and / or, the solvent comprises at least one of terpineol, diethylene glycol butyl ether acetate and dipropylene glycol; And / or, the additive includes at least one of a defoamer, a dispersant, a wetting agent, an anti-aging agent, and a leveling agent.
8. The method for preparing silver-coated iron low-temperature silver paste according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) mixing a solvent and a curing agent under magnetic stirring to obtain a first mixture; (2) mixing the first mixture obtained in step (1) with epoxy resin in a double planetary mixer, and then adding silver powder, silver-coated iron powder, curing accelerator and additives to obtain a second mixture; (3) The second mixture obtained in step (2) is dispersed on a three-roll mill, and then filtered and de-bubbled.
9. The method for preparing the silver-clad iron low-temperature silver paste according to claim 8, characterized in that: In the step (2), the mixing temperature in the double planetary mixer is 0 to 30° C.; And / or, in the step (3), the number of dispersion times on the three-roll mill is 3 to 5 times.
10. Use of the silver-coated iron low-temperature silver paste according to any one of claims 1 to 7 or the silver-coated iron low-temperature silver paste prepared by the preparation method according to claim 8 or 9 in silicon heterojunction batteries.
Citation Information
Patent Citations
Electrocondution slurry of positive electrode of solar cell and preparing method thereof
CN103650238A
Mixed metal powder, preparation method, conductive silver pulp and use
CN106876000A
Ageing resistant composite silver electrode slurry for crystalline silicon solar cells and preparation method for ageing resistant composite silver electrode slurry
CN108777185A
Low-resistivity low-temperature solar silver paste and preparation method thereof
CN114464342A